Jean-Henry D'Anglebert and the Seventeenth-Century Clavecin School - Scheibert, Beverly (Indiana University Press, 1985)
Jean-HenryD'Anglebert, who was active at the court of Louis XIV of France, was one of the most significant musicians of his time. His music is characterized by a superb sense of rhythm, a highly deve!oped harmonic language, and luxuriant ornamentation. Pièces de clavecin of l689, his only published work, contains a table of 29 ornaments, many of which D'Anglebert devised and on which much of his fame rests. Beverly Scheiberta lso examines D'Anglebert's important contributions to the unmeasured prelude, organ composition, and transcription. She discusses classical suite order in France and devotes a long chapter to analyzing the various keyboard dances. Her book is a valuable reference work and a lively acmunt of a unique age.